Identify the Most Suitable Sources of Protein and Their Costs for the Dr. Poons Metabolic Diet Program - Poon, Pat; Lau, Paul (Archives of Clinical and Biomedical Research, 2017)
The objective of the Dr. Poon’s Metabolic Diet Clinic is to help patients improve their obesity related medical conditions through lifestyle modifications. One of the modifications is nutrition. Patients are counseled on the importance of the essential nutrients and to avoid the foods that promote obesity and disease. Human must ingest protein to survive, but protein can be expensive. Patients who have limited food budgets may find it hard to maintain a high protein, low carbohydrate lifestyle. Furthermore, not all protein sources are equal in their biological values. This study tries to identify protein sources that have good biological values and are relatively inexpensive, so our patients can utilize their food budget wisely.